Muscle activation and intermuscular coherence during forward and backward pedaling - Mei-Yi Lee; Ray-Yau Wang; Shu-Shyuan Hsu; Wen-Wen Yang; Shu-Shi Chen; Yea-Ru Yang (Chinese Journal of Physiology, 2020)
The purpose of this study was to investigate muscle activity and intermuscular coherence of the rectus femoris (RF) and biceps femoris (BF) during forward (FW) and backward (BW) pedaling. Sixteen healthy volunteers performed FW and BW pedaling in 30, 45, and 60 revolutions per minute (RPM), while electromyographic (EMG) signals of the RF and BF were recorded bilaterally to determine integral EMG and intermuscular coherence. BW pedaling showed a statistically significant larger EMG activity on the left BF (P = 0.023) in 30 RPM; on the left BF (P = 0.01), right BF (P = 0.05), and right RF (P = 0.006) in 45 RPM, and on the left BF (P = 0.014) and right RF (P = 0.011) in 60 RPM than FW pedaling. In 45 RPM, higher coherence was demonstrated on the left leg (P = 0.011) during the left flexor and right extensor phases and on the right leg (P = 0.043) during the right flexor and left extensor phases in BW compared with FW pedaling. In 60 RPM, higher coherence was observed on both legs (left, P = 0.037; right, P < 0.001) during the left flexor and right extensor phases in BW compared with FW pedaling. Our results suggest that BW pedaling increased the muscle activity of both biarticular muscles and intermuscular coherence.